Pengaruh STARA Awareness Terhadap Individual Competitive Productivity: Peran Mediasi Work Engagement, Organizational Commitment, dan Job Autonomy - Novianti, Yunia; Savitri, Elok (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Employee assessment of the presence of new information technology, namely STARA (Smart Technology, AI, Robotic, and Algorithm), can be a double-edged sword, namely the assessment as a challenge and also an obstacle to work productivity. The main objective of this study is to determine the effect of STARA Awareness through the mediation of work engagement, organizational commitment and job autonomy on individual competitive productivity perceived by employees in the financial services industry in the Greater Jakarta area. Research data was obtained through an online questionnaire of 613 respondents, 79 data were not used due to the cleansing results. A total of 529 data were obtained for testing in this study. Data processing and hypothesis testing used the Covariance-Based Structural Equation Modeling (CB-SEM) method with the LISREL 8.8 application. This study found that the influence of Challenge Appraisal toward STARA Awareness has a significant positive effect on work engagement and job autonomy, hindrance appraisal toward STARA awareness has a positive effect on work engagement, organizational commitment and job autonomy. Organizational commitment has not been able to significantly mediate the effect of challenge appraisal toward STARA awareness on individual competitive productivity. Meanwhile, work engagement, organizational commitment, and job autonomy mediate the influence of hindrance appraisal toward STARA Awareness on individual competitive productivity. This research will provide theoretical and empirical contributions in the field of human resources and organizational development, especially in understanding the influence of employee assessments toward STARA in increasing employee productivity.